Implementasi Metode Pelatihan dalam Program Pengembangan SDM yang Diselenggarakan oleh ACT Consulting - Nuzsep Almigo; Yuyun Yuliyani (Yayasan Kawanad, 2026)
This community service article examines the implementation of human resource development training programs organized by ACT Consulting (ESQ Group), with active participation from an internship student. Partner institutions sought training approaches capable of not merely transferring knowledge, but also cultivating awareness and sustained behavioral change among participants. The activity was carried out through structured observation and facilitation assistance during the training process, employing a range of learning methods — including experiential learning, andragogy-based instruction, multimodal delivery (auditory, visual, and kinesthetic), and structured reflection. Assessment was conducted through participant feedback, observational notes, and post-test scores. Results demonstrate measurable gains in participant engagement, conceptual understanding of training material, capacity to critically evaluate workplace practices, and the ability to construct concrete action plans — all of which reflect higher-order learning outcomes. Beyond its impact on participants, the activity also advanced the professional readiness of the internship student, particularly in understanding adult learning dynamics and applied human resource development. These findings affirm that participatory and reflective training methods hold significant value in community service–based human resource development programs.